Issues in Continuous 24-h Core Body Temperature Monitoring in Humans Using an Ingestible Capsule Telemetric Sensor - Monnard, Cathriona R.; Fares, Elie-Jacques; Calonne, Julie; Miles-Chan, Jennifer L.; Montani, Jean-Pierre; Durrer, Dominique; Schutz, Yves; Dulloo, Abdul G. (Frontiers in Endocrinology, 2017)
Background There is increasing interest in the use of pill-sized ingestible capsule telemetric sensors for assessing core body temperature (Tc) as a potential indicator of variability in metabolic efficiency and thrifty metabolic traits. The aim of this study was to investigate the feasibility and accuracy of measuring Tc using the CorTemp® system. Methods Tc was measured over an average of 20 hours in 27 human subjects, with measurements of energy expenditure made in the overnight fasted state at rest, during standardized low-intensity physical activity and after a 600 kcal mixed meal. Validation of accuracy of the capsule sensors was made ex-vivo against mercury and electronic thermometers across the physiological range (35-40°C) in morning and afternoon of 2 or 3 consecutive days. Comparisons between capsule sensors and thermometers were made using Bland-Altman analysis. Systematic bias, error and temperature drift over time were assessed. Results The circadian Tc profile classically reported in free-living humans was confirmed. Significant increases in Tc (+ 0.2 °C) were found in response to low-power cycling at 40-50W (~ 3-4 METs), but no changes in Tc were detectable during low-level isometric leg press exercise (< 2 METs) or during the peak postprandial thermogenesis induced by the 600 kcal meal. Issues of particular interest include fast ‘turbo’ gut transit with expulsion time of < 15h after capsule ingestion in one out of every 5 subjects and sudden erratic readings in tele-transmission of Tc. Furthermore, ex-vivo validation revealed a substantial mean bias (exceeding ± 0.5°C) between the Tc capsule readings and mercury or electronic thermometers in half of the capsules. When examined over 2 or 3 days, the initial bias (small or large) drifted in excess of ± 0.5°C in one out of every 4 capsules. Conclusion Since Tc is regulated within a very narrow range in the healthy homeotherm’s body (within 1°C), physiological investigations of Tc require great accuracy and precision (better than 0.1 °C). Although ingestible capsule methodology appears of great interest for non-invasively monitoring the transit gut temperature, new technology requires a reduction in the inherent error of measurement and elimination of temperature drift, and warrants more